Association between changes in diet quality from mid-life to late-life and healthy ageing: the Singapore Chinese Health Study. (31st October 2022) - Zhou, Yan-Feng; Lai, Jun S; Chong, Mary Foong-Fong; Tong, Eunice Huiying; Neelakantan, Nithya; Pan, An; Koh, Woon-Puay
Abstract: Background: Few studies have evaluated the association between changes in diet quality from mid-life to late-life and healthy ageing. Methods: We included 12, 316 Chinese adults aged 45–74 years at baseline (1993–1998) from the Singapore Chinese Health Study. Diet quality was measured using the Dietary Approaches to Stop Hypertension (DASH) scores at baseline and follow-up 3 interviews (2014–2016). Healthy ageing was assessed at follow-up 3 interviews, and was defined as absence of specific chronic diseases, good mental and overall self-perceived health, good physical functioning and absence of cognitive impairment, limitations in instrumental activities of daily living or function-limiting pain. Multivariable-adjusted logistic regression models were applied to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for the association between changes in DASH scores and healthy ageing. Results: Compared with participants who maintained relatively stable DASH scores, a >10% decrease in DASH score was associated with a 16% (95% CI, 4–26%) lower likelihood of healthy ageing, whereas a >10% increase in DASH score was associated with a 19% (95% CI, 3–37%) higher likelihood of healthy ageing. Compared with participants who were in the low-score group consistently, participants who increased their DASH scores from moderate-score at baseline to high-score at follow-up 3 had a 53% (95% CI, 21–92%) higher likelihood of healthy ageing, whereas those who were in the high-score group consistently had 108% (95% CI, 71–152%) higher likelihood of healthy ageing. Conclusions: Improving diet quality from mid- to late-life was associated with a higher likelihood of healthy ageing.